2014
DOI: 10.1111/aogs.12322
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy in surgical stage I epithelial ovarian cancer

Abstract: Although increasing, the number of women with surgical stage I disease in Denmark who receive lymphadenectomy remains low, but this did not seem to make a difference to survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…We pooled the relative risks from individual studies using a fixed-effect model and found that SL improved the 5-year OS in all 16 sets of data (RR = 1.08; P = 0.001, 95%CI: 1.03-1.13) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Because of differences in the experimental design, we combined observational studies and RCTs, respectively, as the latter are more convincing than the former.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We pooled the relative risks from individual studies using a fixed-effect model and found that SL improved the 5-year OS in all 16 sets of data (RR = 1.08; P = 0.001, 95%CI: 1.03-1.13) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Because of differences in the experimental design, we combined observational studies and RCTs, respectively, as the latter are more convincing than the former.…”
Section: Discussionmentioning
confidence: 99%
“…Saygili et al (15): had no conflict of interest statement; without long enough follow-up time; high rate of defaulters. The remaining 11 observational studies whose scores ranged from 7 to 9 with a median score of 8 (16)(17)(18)(19)(20)(23)(24)(25)(27)(28)(29) and three RCTs (21-22,26) with scores from 4 to 5 were finally included in our analyses. Figure 1 shows an overview of the process of selection.…”
Section: Literature Search and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our slightly lower one-year survival may partly be explained by the fact that Denmark, in contrary to other countries, did not recommend lymph node resection on stage I patients until 2005. Lymph node removal was nationally implemented in 2012, which is why only 25% of patients in 2005 and 55% of patients in 2011 had this procedure performed [20]. Between 6% and 20% of patients are otherwise expected to have lymph node metastases at time of diagnosis, and in accordance with the FIGO classification, these patients should be reclassified as stage III [12].…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…The aim was to evaluate the Danish nationwide progress in implementing lymphadenectomy for women presenting with tumor(s) macroscopically confined to the ovary, and the effect of lymphadenectomy on the overall survival. The study concluded that the national number of lymphadenectomies was too low, although increasing, and that the effect of lymphadenectomies on overall survival was not significant 9. The results of the study formed the basis for a very intense debate about systematic lymphadenectomy and revision of guidelines.…”
Section: Examples Of Researchmentioning
confidence: 97%